Into Multicultural and Virtual Teamwork: Insights from a Tentative Participant Observation Study in an East Asian Context - Lei, Zhichao; Jin, Huiling (International Journal of Advanced Corporate Learning (iJAC), 2025)
Extending an earlier conference paper by the authors, this report of a participant observation study provides an in-depth discussion on how cultural dimensions and hyper-personal effects might function in a specific context of computer-based communication (CMC) for remote teamwork. Adopting a cyber-ethnographical approach, a researcher engaged in a virtual group, which was working with a Consulate General in Shanghai, China, to observe the intragroup CMC behaviors, interactions, and practices of the participants, while also being involved in the teamwork. The group members were from either China or South Korea, mainly working remotely with one another and rendering this temporary workforce both multicultural and virtual. Paralleling the job tenure, a considerable amount of experience materials had been accumulated, as the product of a nearly 1-year data collection, which laid the foundation for a critical reflection and ad hoc analysis. Insights were drawn from the participant observation to address what could be the most suitable mode of teamwork for a certain multicultural and virtual group. Moreover, limitations of the present study were discussed; and implications were provided for multicultural and virtual teamwork, within and beyond the East Asian context.